Synthetic tetracycline-controllable shRNA targeting long non-coding RNA HOXD-AS1 inhibits the progression of bladder cancer. Issue 1 (December 2016) - Li, Jianfa; Zhuang, Chengle; Liu, Yuchen; Chen, Mingwei; Chen, Yincong; Chen, Zhicong; He, Anbang; Lin, Junhao; Zhan, Yonghao; Liu, Li; Xu, Wen; Zhao, Guoping; et al.
Abstract Background Long non-coding RNAs (lncRNAs) have been proved to act as key molecules in cancer development and progression. Dysregulation of lncRNAs is discovered in various tumor tissues and cancer cells where they can serve as oncogenes or tumor suppressors. Long non-coding RNA HOXD-AS (HOXD cluster antisense RNA 1) has recently been identified to be involved in the development of several cancers including neuroblastoma, adenocarcinomas and breast cancer. However, the role of HOXD-AS1 in bladder cancer remains unknown. Methods The synthetic tetracycline-controllable shRNA was used to modulate the level of HOXD-AS1 by adding different concentrations of doxycycline (dox). RT-qPCR was used to detect the expression level of HOXD-AS1. Cell proliferation was determined by CCK-8 assay and EdU incorporation experiment when HOXD-AS1 was knocked down. We used wound-healing assay for detecting the effect of HOXD-AS1 on cell migration. Eventually, cell apoptosis was determined by caspase 3 ELISA assay and flow cytometry assay. Results In this study, we found that the expression level of HOXD-AS1 was significantly increased in bladder cancer tissues and cells. Furthermore, high expression of HOXD-AS1 was significantly related to tumor size, histological grade and TNM stage. In vitro assays confirmed that knockdown of HOXD-AS1 suppressed cell proliferation/migration and increased the rate of apoptotic cell in bladder cancer cells. At last, we used the important element of synthetic biology, tetracycline(tet)-controllable switch, to construct tet-controllable shRNA vectors which can modulate the expression of HOXD-AS1 in a dosage-dependent manner. Conclusions Our research suggested that high expression of HOXD-AS1 may be involved in the bladder cancer carcinogenesis through inhibiting the phenotypes and activating endogenous cancer-related molecular pathways. Therefore, HOXD-AS1 may act as an oncogene and provide a potential attractive therapeutic target for bladder cancer. In addition, the synthetic tetracycline-controllable shRNA may provide a novel method for cancer research in vitro assays.